Development of a Novel Serum Exosomal MicroRNA Nomogram for the Preoperative Prediction of Lymph Node Metastasis in Esophageal Squamous Cell Carcinoma - Liu, Tong; Du, Lu-Tao; Wang, Yun-Shan; Gao, Shan-Yu; Li, Juan; Li, Pei-Long; Sun, Zhao-Wei; Binang, Helen; Wang, Chuan-Xin (Frontiers in Oncology, 2020)
Background: Preoperative prediction of lymph node (LN) metastasis is accepted as an important independent risk factor for treatment decision-making for esophageal squamous cell carcinoma (ESCC) patients. This study aimed to develop a non-invasive nomogram to identify LN metastasis preoperatively in ESCC patients. Methods: Construction of the nomogram involved 3 sequential phases with independent patient cohorts. In discovery phase (N = 20), LN metastasis-associated miRNAs were selected from next-generation sequencing (NGS) assay of human ESCC serum exosome samples. In training phase (N = 178), a nomogram which incorporated exosomal miRNA model and clinicopathologic was developed by multivariate logistic regression analysis to preoperatively predict LN status. In the validation phase (n = 188), we validated the predicted nomogram’s calibration, discrimination and clinical usefulness. Results: Four differently expressed miRNAs (chr 8-23234-3p, chr 1-17695-5p, chr 8-2743-5p and miR-432-5p) were screened in the serum exosome samples from ESCC patients with or without LN metastasis. Subsequently, an optimized 4-exosomal miRNA model was constructed and validated in clinical cohort, which could effectively identify ESCC patients with LN metastasis, and was significantly superior to preoperative computed tomography (CT) report. In addition, a clinical nomogram consisting of the 4-exosomal miRNA model and CT-report was established in the training set, which performed well in both training and validation cohorts (AUC: 0.880 and 0.869, respectively). Hosmer-Lemeshow test and decision curve analysis implied the clinical applicability of the nomogram. Conclusion: Our novel non-invasive nomogram is a robust prediction tool with promising clinical potential for preoperative prediction of LN metastasis, especially in T1 stage ESCC patients.